METHODS FOR IMPROVING LISTENING SKILLS IN ENGLISH LANGUAGE CLASSES - Djurayeva Dilfuza Bakhtiyarovna (Bright Mind Publishing, 2026)
This article examines effective methods for improving listening skills in English language classes. Listening is considered one of the most essential yet challenging components of language learning, as it directly influences learners’ speaking, reading, and writing abilities. The study highlights the importance of systematic and purposeful listening activities, including the use of authentic audio materials, multimedia resources, interactive tasks, and communicative exercises. Particular attention is given to pre-listening, while-listening, and post-listening strategies that help learners better understand spoken English, develop concentration, and expand vocabulary. The article also emphasizes the role of teachers in creating a supportive learning environment and adapting listening tasks to students’ proficiency levels. The proposed methods aim to enhance learners’ comprehension skills, motivation, and overall communicative competence in English.
Keywords: Listening skills, English language teaching, audio materials, communicative competence, language learning strategies, listening comprehension.